2012
DOI: 10.3329/jsr.v4i3.10777
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Textile Wastewater by Coagulation Precipitation Method

Abstract: Treatment of textile effluent, collected from Sattar Textile located at Chandra under Gazipur district, Bangladesh was carried out by chemical coagulation and precipitation method. The highly alkaline (pH=12.0) reddish orange colored effluent was characterized by chemical oxygen demand (COD) 1638 mg O 2 /L; total suspended solids (TSS) 9.76 g/L; total dissolved solids (TDS) 6.62 g/L and turbidly 31.24 FTU. In the present study, polyaluminium chloride (PAC) and SAFI (described in the results and discussions par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Effluents comprise large quantities of toxic and difficult to treat substances derived from the dyeing and finishing processes. (Al‐Kdasi, Idris, Saed, & Guan, ; Sabur, Khan, & Safiullah, ). The most pertinent problem of textile industry wastewater is the use of dye to impart color (Qadir & Chhipa, ).…”
Section: Introductionmentioning
confidence: 99%
“…Effluents comprise large quantities of toxic and difficult to treat substances derived from the dyeing and finishing processes. (Al‐Kdasi, Idris, Saed, & Guan, ; Sabur, Khan, & Safiullah, ). The most pertinent problem of textile industry wastewater is the use of dye to impart color (Qadir & Chhipa, ).…”
Section: Introductionmentioning
confidence: 99%
“…Poor coagulant species does not participate effetivelly in coagulation and consequently poor COD removal takes place. In earlier studies reported by various investigators for treatment of pulp and paper mill wastewater [25], MWW [26], distillery wastewater [20] and textile industry effluent [27], the treatment efficiency was much in the range of pH 5 to 8.…”
Section: Amentioning
confidence: 95%
“…Further increase of the alum dose from 50 to 60 mM decreases COD reduction by 78% and color reduction by 72%, respectively. Therefore, the optimum dose of alum that enhanced maximum removal of COD and color was taken as 50 mM [46].…”
Section: Effect Of Dosing (Current Density and Mass Loading)mentioning
confidence: 99%